152k views
0 votes
Help please help me please

Help please help me please-example-1

1 Answer

5 votes

(x , y → (x - 5, y - 3)

the coordinates of S(1 , 5),T(1,1), U(4, 1)

the coordinates of the image are S'( - 4, 2), T'( - 4, - 2), U'( - 1 , - 2)

consider the difference in the x- coordinates of the original to the image

1 → - 4 = - 5, 1 → - 4 = - 5, 4 → - 1 = - 5

so the x- coordinate rule is x - 5

now consider the difference in the y- coordinates of the original to the image.


5 → 2 = - 3, 1 → - 2 = - 3, 1 → - 2 = -3

so the y- coordinate rule is y - 3

hence (x, y) → (x - 5, y - 3)


User Mwaa Joseph
by
5.8k points